Barriers and Facilitators to Implementing Immediate Postpartum Contraceptive Implant Programs: A Formative Implementation Research - Sothornwit J; Lumbiganon P; Saranrittichai K; Sangkomkamhang U; Singhdaeng T; Jampathong N (Dove Medical Press, 2022)
Jen Sothornwit,1 Pisake Lumbiganon,1 Kesinee Saranrittichai,2 Ussanee Sangkomkamhang,3 Thanyarat Singhdaeng,4 Nampet Jampathong5 1Department of Obstetrics and Gynaecology, Faculty of Medicine, Khon Kaen University, Khon Kaen, Thailand; 2Department of Health Behavior and Health Promotion, Faculty of Public Health, Khon Kaen University, Khon Kaen, Thailand; 3Department of Obstetrics and Gynecology, Khon Kaen Hospital, Khon Kaen, Thailand; 4Department of Obstetrics and Gynecology, Nam Phong Hospital, Khon Kaen, Thailand; 5Cochrane Thailand, Faculty of Medicine, Khon Kaen University, Khon Kaen, ThailandCorrespondence: Jen Sothornwit, Department of Obstetrics and Gynaecology, Faculty of Medicine, Khon Kaen University, Khon Kaen, Thailand, Email jensoth@kku.ac.thObjective: This study sought to identify the factors that act as barriers and facilitators to developing and implementing Immediate postpartum (IPP) insertion of contraceptive implants service according to the Consolidated Framework for Implementation Research (CFIR).Methods: We conducted in-depth interviews and focus group discussions to explore IPP contraceptive implantation programs implemented in community, regional, and university hospitals in Thailand. The CFIR was used to guide the data collection and analyses.Results: All CFIR domains were found to have an impact on planning and implementation. Out of 38 constructs, nine were identified as either barriers or facilitators, and four were determined to be both. Barriers included an insufficient training budget, lack of policy to support non-teenagers, disconnect among organizations, and lack of knowledge on the part of the clients. Facilitators included the relative advantage of implants over other contraceptive methods, reimbursement policy, laws that promote teenage autonomy, setting IPP implants as a key performance indicator (KPI), identifying project champions, and educating clients through antenatal counseling or multimedia intervention.Conclusion: Barriers and facilitators to the successful implementation of an IPP contraceptive implant program were identified. In order to successfully implement this service, modifiable barriers should be overcome and facilitators should be strengthened. Strategies tailored to the local context should be developed to ensure the sustainability of the program. Educating clients is crucial and need both hospital- and community interventions.Keywords: contraceptive implants, implementation science, influencing factors, long-acting reversible contraception, postpartum contraception